2010
DOI: 10.1016/j.scitotenv.2010.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing DOC trends in soil solution along the hillslopes at two IM sites in southern Sweden — Geochemical modeling of organic matter solubility during acidification recovery

Abstract: This is an author produced version of a paper published in Science of The Total Environment. This paper has been peer-reviewed and is proofcorrected, but does not include the journal pagination.Citation for the published paper: Löfgren, S., Gustafsson, J. P., Bringmark, L. (2010) Recently, a hypothesis was presented on how various spatial and temporal factors affect 4 the DOC dynamics. It was concluded that declining sulphur deposition and thereby 5 increased DOC solubility, is the most important driver for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…DOC concentrations in soil water in southern Sweden and Norway have also been shown to be either decreasing or remaining fairly constant, especially in soil water from or below the B-horizon Wu et al 2010). Based on data from Aneboda and Kindla, it has been shown that soil water DOC concentrations are strongly influenced by pH, IS, and Al dynamics (Löfgren et al 2010b). …”
Section: Effects Of S Deposition Decline At Each Of the Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…DOC concentrations in soil water in southern Sweden and Norway have also been shown to be either decreasing or remaining fairly constant, especially in soil water from or below the B-horizon Wu et al 2010). Based on data from Aneboda and Kindla, it has been shown that soil water DOC concentrations are strongly influenced by pH, IS, and Al dynamics (Löfgren et al 2010b). …”
Section: Effects Of S Deposition Decline At Each Of the Sitesmentioning
confidence: 99%
“…However, based on soil water data from southern Sweden, the postulated causal link between recovery from anthropogenic acidification and increases in surface water DOC has been challenged (Löfgren et al 2010b;Löfgren and Zetterberg 2011). Instead, the data indicate that climatic drivers, including precipitation, temperature, and changes in hydrological flow patterns, are the most important factors affecting surface water DOC concentrations (Erlandsson et al 2008;Sarkkola et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, over-reliance on simple models and purely statistical criteria may lead to overly simplistic views of the environment. If nothing else, it can be argued that more than 30 years of research into surface water DOC, and its links to acidification, acidity, climate and hydrology (Krug and Frink 1983;Laudon et al 1999;Erlandsson et al 2008Erlandsson et al , 2010Lepistö et al 2008;Clark et al 2010;Haaland et al 2010;Haei et al 2010;Löfgren et al 2010b;Löfgren and Zetterberg 2011), has shown that numerous factors influence or covary with surface water DOC. So, we must conclude that, on the basis of our current understanding, reality is over-determined but that models can be a useful tool for environmental hypothesis testing and understanding.…”
Section: Discussionmentioning
confidence: 99%
“…At many sites, while SO 4 2-deposition has been declining, the climate has warmed and runoff rates have changed. Geochemical modeling of the DOC dynamics in soil water at two of the Swedish integrated monitoring (IM) sites has identified a complex pattern of relationships between DOC and SO 4 2-deposition-driven changes in pH, ionic strength and aluminum chemistry, which can result in both increasing and decreasing trends in soil water [DOC] (Löfgren et al 2010b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation